The Costa Rican business sector's concepts of the transfer of German dual training - Daniel Láscarez-Smith; Johannes K. Schmees (Universidad de Costa Rica, 2021)
This article analyzes the tripartite social dialogue of an inter-institutional commission in Costa Rica, which took place from February 27 to September 1, 2017. During this time the Costa Rican state the business sector and unions discussed ways to implement dual vocational education and training (VET) in Costa Rica, using the German model as a reference. Here, the focus is on the business sector's concepts regarding if and how the German dual VET model should be transferred to Costa Rica. the findings are based on two interviews with Costa Rican business representatives and the observation of dialogue table meetings with representatives from the state, the business sector and unions. Based on the premise that discourses express and influence social practices, it is analyzed how the structure of the business sector's arguments relate to Toulmin's model of argumentation. It is concluded that from the Costa Rican business sector's point of view, the policy of dual education in VET is essential to gain economic strength in a global market. However, for these business groups, the model must be "tropicalized" in a way that redefines some of the bases of the German reference model, such as union participation, distribution of training costs as well as the legal status of the apprentice. Therefore, it is concluded that the discussion on the dual model of VET was used as a window of opportunity to promote reforms that would favor the business sector.